The Use of Babasan Idiomatic Expressions in the Short Stories of Cindulamg Aya Kembang by Aam Amilia - Miza Rohmani Putri; Raisya Revalia Putri; Yayat Sudaryat; Zulfikar Alamsyah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to describe the forms and meanings of idioms in the carpon Di Cindulang aya Kembang by Aam Amilia. This study is qualitative in nature. The data used in this study were taken from the carpon. The data consisted of words, sentences, or expressions containing idiomatic babasan. The data collection technique used was literature study. The results show that there are several types of idiomatic expressions in the short story Di Cindulang aya Kembang by Aam Amilia, namely idiomatic expressions wangun rundayan, babasan wangun kantetan, babasan wangun frasa, babasan miraga, babasan misato, babasan mituwuhan, babasan mialam, and babasan mibarang. These idioms are used to state, conclude, emphasize, satirize, and criticize something. Reconstructing short stories into mini stories requires not only a deep understanding of narrative structure, but also sensitivity to aesthetic values and language rhythm.